Determination of a Bacillus velezensis strain for controlling soybean root rot. Issue 5 (4th May 2017) - Huang, M. H.; Zhang, S. Q.; Di, G. L.; Xu, L. K.; Zhao, T. X.; Pan, H. Y.; Li, Y. G.
ABSTRACT: Bacteria were obtained from soybean rhizosphere soil. And control effect of a tested isolate for controlling soybean root rot infected by Fusarium oxysporum was evaluated. The selected bacterial isolate exhibited the greatest inhibition of F. oxysporum in the laboratory and substantially reduced soybean root rot in pot-controlled assays.